Afectaciones psicosociales debido a la pandemia en estudiantes y docentes de una institución de educación superior en Cartago Valle (2023)
When people are faced with non-normative events, what is expected is that internal and external factors are presented, in addition to the ways they are expressed, to psychology it is important that they can be analyzed to contemplate the ways in which coping is done, in the present investigations it is proposed as objetive to know the psychosocial affectations due to the pandemic on students and teachers of a higher education institution, which is developed through the mixed type methodology, the instruments used were designed basedon sociodemographic characteristics for the quantitative stage with the participation of 19 teachers and university students; and for the qualitative stage there were 3 university professors and 3 university students who answered the semi-structured interview.